Cardiac defects, nuchal edema and abnormal lymphatic development are not associated with morphological changes in the ductus venosus. (October 2016) - Burger, Nicole B.; Haak, Monique C.; Kok, Evelien; de Groot, Christianne J.M.; Shou, Weinian; Scambler, Peter J.; Lee, Youngsook; Cho, Eunjin; Christoffels, Vincent M.; Bekker, Mireille N.
Abstract: Background: In human fetuses with cardiac defects and increased nuchal translucency, abnormal ductus venosus flow velocity waveforms are observed. It is unknown whether abnormal ductus venosus flow velocity waveforms in fetuses with increased nuchal translucency are a reflection of altered cardiac function or are caused by local morphological alterations in the ductus venosus. Aim: The aim of this study was to investigate if the observed increased nuchal translucency, cardiac defects and abnormal lymphatic development in the examined mouse models are associated with local changes in ductus venosus morphology. Study design: Mouse embryos with anomalous lymphatic development and nuchal edema ( Ccbe1 −/− embryos), mouse embryos with cardiac defects and nuchal edema ( Fkbp12 −/−, Tbx1 −/−, Chd7 fl / fl ;Mesp1Cre, Jarid2 −/− NE+ embryos) and mouse embryos with cardiac defects without nuchal edema ( Tbx2 −/−, Fgf10 −/−, Jarid2 −/− NE − embryos) were examined. Embryos were analyzed from embryonic day (E) 11.5 to 15.5 using markers for endothelium, smooth muscle actin, nerve tissue and elastic fibers. Results: All mutant and wild-type mouse embryos showed similar, positive endothelial and smooth muscle cell expression in the ductus venosus at E11.5–15.5. Nerve marker and elastic fiber expression were not identified in the ductus venosus in all investigated mutant and wild-type embryos. Local morphology and expression of the used markers were similar in the ductus venosus in all examined mutant and wild-type embryos. Conclusions: Cardiac defects, nuchal edema and abnormal lymphatic development are not associated with morphological changes in the ductus venosus. Ductus venosus flow velocity waveforms most probably reflect intracardiac pressure. Highlights: Cardiac defects, nuchal edema and abnormal lymphatic development are not associated with changed ductus venosus morphology. Ductus venosus flow velocity waveforms most probably reflect intracardiac pressure